FRI0463 ENTHESITIS, DACTYLITIS, AND AXIAL DISEASE IN PSORIATIC ARTHRITIS (PSA): IMPACT ON PATIENT QUALITY OF LIFE AND WORK PRODUCTIVITY. (June 2019) - Walsh, Jessica A.; Ogdie, Alexis; Michaud, Kaleb; Peterson, Steve; Holdsworth, Elizabeth; Karyekar, Chetan; Booth, Nicola; Kemp, Jessalyn; Chakravarty, Soumya D.; Kafka, Shelly; Gossec, Laure
Abstract : Background: PsA is a chronic, inflammatory disease characterised by peripheral arthritis, axial disease, dactylitis, enthesitis and skin and nail psoriasis. The impact of skin and joint components of the disease on quality of life and work productivity has been studied (1, 2) but the impact of other manifestations has not. Objectives: To assess the impact of enthesitis, dactylitis, and axial disease on quality of life and work productivity in PsA patients. Methods: Cross-sectional study among patients with PsA recruited by rheumatologists and dermatologists in France, Germany, Italy, Spain, UK, and US. Data were collected from Jun-Aug 2018 via physician-completed patient record forms and patient self-completed forms. Physicians recorded (Yes/No) if patients currently presented with enthesitis, dactylitis, inflammatory back pain (IBP), and sacroiliitis (identified by x-ray or MRI). Multiple linear regression analyses were used to examine the impact of these manifestations on patient reported outcomes (PROs) including EQ-5D index, EQ-5D VAS, HAQ-DI, PsAID12, and WPAI. Models were adjusted for age, gender, number of joints affected, and time since diagnosis. There was no imputation of missing data. Results: The sample included 1103 patients: mean age 47.6 [SD 13.2] years, 46% were female, 58% were working full time. Mean number of joints affected by PsA was 3.8 (SD 5.2), and 54.9% were receiving biologic treatment. Enthesitis (present in 6.3% of patients), dactylitis (8.0%) and IBP (12.6%) were associated with worse outcomes overall (Table 1 ); sacroiliitis (3.9%) was linked to worse physical function and quality of life. Conclusion: In a multi-national, real-world PsA population, enthesitis, dactylitis, IBP, and sacroiliitis were significantly associated with worse patient quality of life and/or work productivity across a range of PROs independent of the number of joints affected. These manifestations should be considered alongside skin and joint components in order to optimize patient outcomes. References: [1] Borman P, et al. Clin Rheumatol. 2007;26(3):330–4. [2] de Vlam K, et al. Rheumatol Ther. 2018;5(2):423–36. Disclosure of Interests: Jessica A. Walsh Grant/research support from: Abbvie, Pfizer, Consultant for: Abbvie, Celgene, Lilly, Novartis, Alexis Ogdie Grant/research support from: (To my university) Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Consultant for: AbbVie, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly and Company, Novartis, Pfizer, and Takeda, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly, Novartis, Pfizer Inc, Takeda, Consultant for: Abbvie, Amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda, Consultant for: Abbvie, Amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda, Kaleb Michaud Grant/research support from: Pfizer (within past 2 years), Steve Peterson Shareholder of: Janssen, Employee of: BMS (2000-2002), Janssen (2002-present), Elizabeth Holdsworth Employee of: Adelphi Real World, Chetan Karyekar Shareholder of: J&J, Employee of: Janssen Scientific Affairs, LLC, Abbott, BMS, Novartis, Nicola Booth Employee of: Adelphi Real World, Jessalyn Kemp Employee of: Adelphi Real World, Soumya D Chakravarty Shareholder of: Johnson & Johnson, Employee of: Johnson & Johnson, Shelly Kafka Shareholder of: J&J, Employee of: J&J, Laure Gossec Grant/research support from: AbbVie, BMS, Celgene, Janssen, Lilly, MSD, Novartis-Sandoz, Pfizer, Sanofi, and UCB, Consultant for: AbbVie, Biogen, BMS, Celgene, Janssen, Lilly, MSD, Nordic Pharma, Novartis-Sandoz, Pfizer, Roche, Sanofi, and UCB, Consultant for: L Gossec has received honoraria from Celgene as investigator for this study